Konsentrasi Merkuri (Hg) pada Sedimen Amalgamasi yang Dibuang ke Badan Air dari Aktivitas Penambangan Emas Tradisional di Desa Tambang Sawah Kabupaten Lebong - Mulyadi, Irwan; Indrawijaya, Budhi; Adlin, Irman Ansari (Politeknik Negeri Lhokseumawe, 2025)
Traditional gold mining activities in Tambang Sawah Village, Lebong Regency, Bengkulu Province, produce tailings waste with high concentrations of mercury (Hg). This waste is discharged directly into the Air Putih River without prior treatment. This research aims to measure mercury levels in the tailings and analyze the relationship between the quantity of discarded tailings and the Hg contamination levels in river sediments. Sampling was conducted following the JPHA method, and Hg level analysis was based on NOAA and ASTM guidelines. The results indicate that all tailings samples from 10 discharge points exceeded the mercury contamination threshold. The total estimated tailings discharged each week reached 1,600 kg from 40 miners. The highest concentrations were found at points with the most miners. A laboratory test on 10 tailing samples collected from discharge points along the Air Putih River showed that all samples contained mercury (Hg), with the highest concentration reaching up to 266 ppm.